MySQL high availability - Bell, Charles A. 1962- (O'Reilly Media, 2010)
Server bottlenecks and failures are a fact of life in any database deployment, but they don't have to bring everything to a halt. MySQL has several features that can help you protect your system from outages, whether it's running on hardware, virtual machines, or in the cloud. MySQL High Availability explains how to use these replication, cluster, and monitoring features in a wide range of real-life situations. Written by engineers who designed many of the tools covered inside, this book reveals undocumented or hard-to-find aspects of MySQL reliability and high availability -- knowledge that's essential for any organization using this database system. Explore the binary log, a file for replication that helps in disaster recovery and troubleshooting Get techniques for improving response time and handling large data sets Monitor database activity and performance, as well as major operating system parameters Keep track of what masters and slaves are doing, and deal with failures and restarts, corruption, and other incidents Automate key tasks with code from an open source library written by the authors Learn techniques for using MySQL in virtualized environments, such as Amazon Web Services Use MySQL Cluster to achieve high availability "MySQL replication is widely deployed but has never been adequately explained. This book changes that."-- Mark Callaghan, MySQL contributor and leader of MySQL engineering efforts at a few of the world's largest Internet companies.